Study Of Structuralism With Robert Stanton's Perspective In A Novel Every Night Is Separated By Alfiansyah On Language Learning Based On Literature - Widyatmike Gede Mulawarman; Nina Queena Putri; Endang Dwi Sulityowati; Alfian Rokhmansyah; Herdita Noor Wanda (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Robert Stanton's structuralism is a study that focuses on the means of storytelling by looking at gender perspective as a problem in the novel that will be discussed in this study. This study aims to (1) describe Robert Stanton's Structuralism in the form of a literary means of building the novel Every Night is Sepi by Alfiansyah; (2) describing the gender perspective in the novel Every Night is Sepi by Alfiansyah. This study uses a qualitative approach with the analysis of the content of Robert Stanton's model. The results showed structural elements focusing on the means of the story and gender perspective as follows: Literary means are things that are utilized by the author in choosing and arranging the details of the story. The novel Every Malam is Sepi is built by excellent literary means because it meets all elements, namely: title, point of view, style and tone, symbolism, and irony. The gender perspective in the novel Every Night is Sepi is gender equality and gender injustice. The novel's gender injustices are marginalization, subordination, stereotypes, violence against women, and the double burden